Hydrodynamic assessment of seashell blocks for coastal protection - Nur Kamalia Khairunnisa’ Jazrim Shah; Nurul Rabitah Daud; Lee, Wei Koon; Ganugapenta Sreenivasulu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Traditional coastal protection strategies frequently depend on man-made structures that may have negative environmental impacts and have limited long-term sustainability. There is a pressing need to develop a new approach to address the issues. This study aims to investigate the stability of seashell blocks when exposed to wave forces, the behaviour of seashells when partially submerged, fully immersed, and exposed, and how seashells react to regular and irregular waves. Multiple experiments with varied wave amplitude and frequency are performed using a wave flume maker to evaluate the attenuation of waves. In this study, seashells were used as models with the application of a flume wavemaker in UiTM Shah Alam’s laboratory. The models reproduce the effects of ocean waves. However, the research is restricted by the flume wavemaker’s dimensions, which are 20 meters in length with the generating equipment and a maximum water depth of 0.4 meters. Parameters including frequency, wavelength, and amplitude were measured using pressure sensors and wave probes. The findings show that the partially submerged seashells performed better in regions with shorter coastal waves. The width of a submerged breakwater’s crest can be cut in half by using seashell blocks. The findings can significantly facilitate the development of long-lasting and efficient coastal protection measures, as well as the design, construction, and monitoring of seashell block structures. Additional research is required to determine the cost, lifespan, and effectiveness of shell blocks in different coastal environments.